21. THE RELATIONSHIP BETWEEN HEALTHCARE SERVICE QUALITY AND PATIENT SATISFACTION AT CHILDREN HOSPITAL 2 (Vietnam Journal of Community Medicine, 2025)
Background: Healthcare service quality plays a vital role in determining patient satisfaction. Evaluating this relationship helps healthcare providers enhance service effectiveness and patient experience. This study aimed to examine the relationship between healthcare service quality and patient satisfaction at Children Hospital 2, Ho Chi Minh City.Methods: A mixed-methods design was employed, integrating both qualitative and quantitative approaches. Quantitative data were collected via structured surveys from patients and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Six service quality dimensions were examined: Doctor’s Communication, Tangibles, Responsiveness, Empathy, Assurance, and Reliability.Results: All six service quality factors showed statistically significant and positive impacts on patient satisfaction. Among them, “Doctor’s Communication” (w = 0.725) and “Assurance” (w = 0.680) were the most influential contributors to satisfaction levels. The model explained 78.5% of the variance in overall patient satisfaction.Conclusion: The findings confirm the critical role of healthcare service quality in shaping patient satisfaction, with a particular emphasis on communication skills and professional competence of healthcare staff. These insights provide a scientific foundation for Children Hospital 2 and similar institutions to formulate targeted strategies for service improvement and patient-centered care.
Keywords: Healthcare service quality, patient satisfaction, Children Hospital 2.